Design and Implementation of an Additively Manufactured Reactor Concept for the Catalytic Methanation - Hauser, Alexander; Neubert, Michael; Feldner, Alexander; Horn, Alexander; Grimm, Fabian; Karl, Jürgen (Applied Sciences, 2022)
The methanation process is discussed as one way to chemically store renewable energy in a future energy system. An important criterion for its application is the availability of compact, low-cost reactor concepts with high conversion rates for decentralized use where the renewable energy is produced. Current research focuses on the maximization of the methane yield through improved temperature control of the exothermic reaction, which attempts to avoid both kinetic and thermodynamic limitations. In this context, traditional manufacturing methods limit the design options of the reactor and thus the temperature control possibilities. The use of additive manufacturing methods removes this restriction and creates new freedom in the design process. This paper formulates the requirements for a novel methanation reactor and presents their implementation to a highly innovative reactor concept called ‘ADDmeth’. By using a conical reaction channel expanding from Ø 8 to 32 mm, three twisted, expanding heat pipes (Ø 8 mm in evaporation zone, Ø 12 mm in condenser zone) and a lattice structure for feed gas preheating and mechanical stabilization of the reactor, the design explicitly exploits the advantages of additive manufacturing. The reactor is very compact with a specific mass of 0.36 kg/kW and has a high share of functional volume of 52%. The reactor development was accompanied by tensile tests of additively manufactured samples with the used material 1.4404 (316 L), strength calculations for stability verification and feasibility studies on the printability of fine structures. Ultimate tensile strengths of up to 750 N/mm2 (at room temperature) and sufficiently high safety factors of the pressure-loaded structures against yielding were determined. Finally, the paper presents the manufactured bench-scale reactor ADDmeth1 and its implementation.
CRIS-Team Scopus Importer:2022-10-07
Keywords: additive manufacturing; catalytic methanation; conic reaction channel; heat pipes; reactor design

Die wasserstoffintensivierte Methansynthese als Möglichkeit der stofflichen Verwertung von Kuppelgasen der Stahlindustrie – das Projekt i³upgrade - Hauser, Alexander; Weitzer, Maximilian; Neubert, Michael; Karl, Jürgen (DGMK Fachtagung „Thermische Konversion – Schlüsselbaustein für zukünftige Energie- und Rohstoffversorgung“, 2019)

Dynamic hydrogen-intensified methanation of synthetic by-product gases from steelworks - Hauser, Alexander; Weitzer, Maximilian; Gunsch, Stephan; Neubert, Michael; Karl, Jürgen (Fuel Processing Technology, 2021)
Steelworks' by-product gases contain significant amounts of carbonaceous species, which can serve as carbon source for Power-to-Gas processes. The COx components from the by-product gases are converted into methane together with renewable hydrogen in a hydrogen-intensified synthesis reaction. Dynamic operation modes of the methanation are discussed to supersede large gas buffer capacities. This paper presents results from a two-stage methanation concept operated with by-product gases from steel industries. The first reactor is designed as heat pipe cooled structured fixed-bed reactor. Both the influence of the volume flow rate and the stoichiometric ratio are examined for different steady-state operating points as well as for dynamic operation modes with repetitive alteration of those two parameters. The two-stage methanation concept provides a consistent product gas quality over a wide syngas power range at slightly over-stoichiometric conditions for both steady-state and dynamic operating conditions. Full methane yield is achieved. The design of the heat pipe cooled structured reactor allows for step changes in syngas power up to 1.6 kW. Catalyst deactivation by coking took place in the first reactor stage during the performed experiments. This happened probably due to unfavourable operating conditions in the carbon formation regime while methanizing CO-rich gases.
CRIS-Team Scopus Importer:2021-03-26
Keywords: By-product gas; Catalyst deactivation; Catalytic methanation; Dynamic; Steelworks

Dynamic methanation of by-product gases from the steel industry in the scope of the project i³upgrade - Hauser, Alexander; Weitzer, Maximilian; Gunsch, Stephan; Neubert, Michael; Karl, Jürgen (Proceedings of the ICPS 19, 2019)

Experimental evaluation of a heat pipe cooled structured reactor as part of a two-stage catalytic methanation process in power-to-gas applications - Neubert, Michael; Hauser, Alexander; Pourhossein, Babak; Dillig, Marius; Karl, Jürgen (Applied Energy, 2018)
Keywords: Catalytic methanation; Reactor concept; Heat pipe; Power-to-gas

Heatpipe-gekühltes Reaktorkonzept für die katalytische Methanisierung in power-to-gas Anwendungen - Neubert, Michael; Hauser, Alexander; Dillig, Marius; Karl, Jürgen (ProcessNet 2018 Jahrestreffen der Fachgruppe EVT, 2018)

Hydrogen intensified synthesis processes to valorise process off-gases in integrated steelworks - Matino, Ismael; Dettori, Stefano; Conde, Amaia Sasian; Colla, Valentina; Petrucciani, Alice; Zaccara, Antonella; Iannino, Vincenzo; Mocci, Claudio; Hauser, Alexander; Kolb, Sebastian; Karl, Jürgen; Haag, Stéphane; et al. (Materiaux et Techniques, 2023)
Integrated steelworks off-gases are generally exploited to produce heat and electricity. However, further valorization can be achieved by using them as feedstock for the synthesis of valuable products, such as methane and methanol, with the addition of renewable hydrogen. This was the aim of the recently concluded project entitled Intelligent and integrated upgrade of carbon sources in steel industries through hydrogen intensified synthesis processes (i3upgrade). Within this project, several activities were carried out: from laboratory analyses to simulation investigations, from design, development and tests of innovative reactor concepts and of advanced process control to detailed economic analyses, business models and investigation of implementation cases. The final developed methane production reactors are, respectively, an additively manufactured structured fixed-bed reactor and a reactor setup using wash-coated honeycomb monoliths as catalyst; both reactors reached almost full COx conversion under slightly over-stoichiometric conditions. A new multi-stage concept of methanol reactor was designed, commissioned, and extensively tested at pilot-scale; it shows very effective conversion rates near to 100% for CO and slightly lower for CO2 at one-through operation for the methanol synthesis. Online tests proved that developed dispatch controller implements a smooth control strategy in real time with a temporal resolution of 1'‰ min and a forecasting horizon of 2'‰ h. Furthermore, both offline simulations and cost analyses highlighted the fundamental role of hydrogen availability and costs for the feasibility of i3upgrade solutions, and showed that the industrial implementation of the i3upgrade solutions can lead to significant environmental and economic benefits for steelworks, especially in case green electricity is available at an affordable price.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Advanced control; Carbon capture and usage; Hydrogen use; Methane synthesis; Methanol synthesis; Process-off gases valorization; Steel; Steelmaking industry sustainability

Hydrogen role in the valorization of integrated steelworks process off-gases through methane and methanol syntheses - Matino, Ismael; Dettori, Stefano; Zaccara, Antonella; Petrucciani, Alice; Iannino, Vincenzo; Colla, Valentina; Bampaou, Michael; Panopoulos, Kyriakos; Rechberger, Katharina; Kolb, Sebastian; Hauser, Alexander; Wolf-Zoellner, Philipp; et al. (Materiaux et Techniques, 2022)
The valorization of integrated steelworks process off-gases as feedstock for synthesizing methane and methanol is in line with European Green Deal challenges. However, this target can be generally achieved only through process off-gases enrichment with hydrogen and use of cutting-edge syntheses reactors coupled to advanced control systems. These aspects are addressed in the RFCS project i(3)upgrade and the central role of hydrogen was evident from the first stages of the project. First stationary scenario analyses showed that the required hydrogen amount is significant and existing renewable hydrogen production technologies are not ready to satisfy the demand in an economic perspective. The poor availability of low-cost green hydrogen as one of the main barriers for producing methane and methanol from process off-gases is further highlighted in the application of an ad-hoc developed dispatch controller for managing hydrogen intensified syntheses in integrated steelworks. The dispatch controller considers both economic and environmental impacts in the cost function and, although significant environmental benefits are obtainable by exploiting process off-gases in the syntheses, the current hydrogen costs highly affect the dispatch controller decisions. This underlines the need for big scale green hydrogen production processes and dedicated green markets for hydrogen-intensive industries, which would ensure easy access to this fundamental gas paving the way for a C-lean and more sustainable steel production.
Created from Fastlane, WoS look-up

Methanisierung von kohlenstoffreichen Kuppelgasen der Stahlindustrie – das Projekt i³upgrade - Hauser, Alexander; Neubert, Michael; Karl, Jürgen (Jahrestreffen der ProcessNet Fachgruppe Hochtemperaurtechnik, 2019)

Optimizing methane and methanol production from integrated steelworks process off-gases through economic hybrid model predictive control - Dettori, Stefano; Matino, Ismael; Iannino, Vincenzo; Colla, Valentina; Hauser, Alexander; Wolf-Zoellner, Philipp; Haag, Stephane (IFAC PAPERSONLINE, 2022)
Within integrated steelworks, process off-gases are important energy carriers. After suitable treatment, they are typically exploited for heating purposes and for production of steam and electricity. However, their main compounds (COx and H2) can also be valorized through synthesis reactors, which provide valuable products, such as methane and methanol, while reducing CO2 emissions. To this aim, large quantities of cheaply and greenly produced hydrogen must be available to enrich process off-gases and make them suitable to the synthesis processes. The enrichment and valorization of process off-gases requires an advanced control system that ensure optimal economic valorization and safe operation of the plants. This paper proposes a solution relying on a dispatch controller based on Economic Hybrid Model Predictive Control, which integrates a set of process models based on physical/chemical laws and machine learning-based models for disturbances forecasting. The controller implements a mixed integer linear programming approach after the linearization of the dynamics of controlled systems every control step. The optimization problem also includes a set of constraints related to the operating condition limits of each equipment. Economic and environmental impacts of the proposed approach are compared with respect to the standard use of process off-gases. The feasibility of the approach strictly depends on the cost of hydrogen, and, in the case of low-cost green electricity sources, the results are highly encouraging. The approach was successfully tested on-line to supervise the operation of pilot methanol and methane reactors.<br
CRIS-Team WoS Importer:2022-06-10
Keywords: Economic Hybrid Model Predictive Control; Integrated Steelworks Process Off-gases; Deep Echo State Networks; Methanol; Methane Synthesis Reactors; Optimized Hydrogen Production

Utilization of Synthetic Steel Gases in an Additively Manufactured Reactor for Catalytic Methanation - Hauser, Alexander; Feldner, Alexander; Treiber, Peter; Grimm, Fabian; Karl, Jürgen (Sustainability, 2023)
The path to European climate neutrality by 2050 will require comprehensive changes in all areas of life. For large industries such as steelworks, this results in the need for climate-friendly technologies. However, the age structure of existing steelworks makes transitional solutions such as carbon capture, utilization and storage (CCUS) necessary as short-term measures. Hence, a purposeful option is the integration of technical syntheses such as methanation into the overall process. This work summarizes hydrogen-intensified methanation experiments with synthetic steel gases in the novel additively manufactured reactor ‘ADDmeth1’. The studies include steady-state operating points at various reactor loads. Blast furnace gas (BFG), basic oxygen furnace gas (BOFG) and three mixtures of these two gases serve as carbon sources. The methanation achieved methane yields of 93.5% for BFG and 95.0% for BOFG in the one-stage once-through setup. The results suggest a kinetic limitation in the case of BFG methanation, while an equilibrium limitation is likely for BOFG. There is a smooth transition in all respects between the two extreme cases. The reaction channel inlet temperature (Formula presented.) showed a large influence on the reactor ignition behavior. By falling below the threshold value, a blow-off occurred during experimental operation. By means of a simulation model, practical operating maps were created which characterize permissible operating ranges for (Formula presented.) as a function of the gas composition and the reactor load.
CRIS-Team Scopus Importer:2023-05-26
Keywords: BFG; BOFG; by-product gas; catalytic methanation; ignition behavior; simulation; temperature profiles

Valorization of steel-work off-gases: Influence of impurities on the performance of Cu-based methanol synthesis catalyst - Heracleous, Eleni; Koidi, Vasiliki; Lappas, Angelos A.; Hauser, Alexander; Haag, Stéphane (Chemical Engineering Journal, 2022)
The use of steel-work off-gases as CO2 source for methanol production is a promising strategy for the decarbonization of the steel industry. In this work, we show that typical impurities, namely S, N, Na, Ca and Fe, reduce the activity of a commercial CuO/ZnO/Al2O3 catalyst by blocking part of the Cu active sites. The extent of the activity loss is proportional to the poison-induced decrease in the exposed Cu surface area, suggesting that the poisons do not modify the nature, but rather the number of active sites. The only deviation is observed for Na, as its strong basicity leads to stronger binding of CO2 on the catalyst surface. Moreover, all catalysts suffer from methanol selectivity losses with time, due to thermal sintering that occurs similarly over the untreated and poisoned samples. Industrial CO2 off-gases can thus be exploited for methanol production after appropriate purification targeted primarily at the removal of metal impurities. The presence of sulfur and nitrogen is less critical to the catalyst performance.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Catalyst poisoning; CO; Commercial CuO/ZnO/Al; Methanol synthesis; Steel-work off-gases

Valorizing Steelworks Gases by Coupling Novel Methane and Methanol Synthesis Reactors with an Economic Hybrid Model Predictive Controller - Hauser, Alexander; Wolf-Zoellner, Philipp; Haag, Stephane; Dettori, Stefano; Tang, Xiaoliang; Mighani, Moein; Matino, Ismael; Mocci, Claudio; Colla, Valentina; Kolb, Sebastian; Bampaou, Michael; Panopoulos, Kyriakos; et al. (Metals, 2022)
To achieve the greenhouse gas reduction targets formulated in the European Green Deal, energy- and resource-intensive industries such as the steel industry will have to adapt or convert their production. In the long term, new technologies are promising. However, carbon capture storage and utilization solutions could be considered as short-term retrofitting solutions for existing steelworks. In this context, this paper presents a first experimental demonstration of an approach to the utilization of process off-gases generated in a steelworks by producing methane and methanol in hydrogen-intensified syntheses. Specifically, the integration of two methane synthesis reactors and one methanol synthesis reactor into a steel plant is experimentally simulated. An innovative monitoring and control tool, namely, a dispatch controller, simulates the process off-gas production using a digital twin of the steel plant and optimizes its distribution to existing and new consumers. The operating states/modes of the three reactors resulting from the optimization problem to be solved by the dispatch controller are distributed in real time via an online OPC UA connection to the corresponding experimental plants or their operators and applied there in a decentralized manner. The live coupling test showed that operating values for the different systems can be distributed in parallel from the dispatch controller to the test rigs via the established communication structure without loss. The calculation of a suitable control strategy is performed with a time resolution of one minute, taking into account the three reactors and the relevant steelworks components. Two of each of the methane/methanol synthesis reactors were operated error-free at one time for 10 and 7 h, respectively, with datasets provided by the dispatch controller. All three reactor systems were able to react quickly and stably to dynamic changes in the load or feed gas composition. Consistently high conversions and yields were achieved with low by-product formation.
CRIS-Team WoS Importer:2022-07-08

Vorschlag einer katalytischen Methanisierung für kleinskalige dezentrale SNG Erzeugung - Neubert, Michael; Hauser, Alexander; Treiber, Peter; Karl, Jürgen (DGMK-Tagung Thermische Konversion - Schlüsselbaustein für zukünftige Energie und Rohstoffsysteme, 2019)